ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN DIKABUPATEN BENGKALIS - Desti Susanti; H.B. Isyandi; Any Widayatsari (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to analyze the effect of economic growth, unemployment rate, per capita expenditure and education on poverty in Bengkalis Regency. This research is a research using time series data from 2011 to 2020. By using a qualitative descriptive method of multiple regression models with simple least squares analysis technique (Ordinary Least Square (OLS). Based on the results of the study, it is known that economic growth has a negative and significant effect on poverty in Bengkalis Regency. This means that when economic growth increases, it will encourage poverty reduction. Unemployment rate has a positive and significant effect on poverty in Bengkalis Regency. This means that changes in the unemployment rate can affect changes in poverty. Expenditure per capita has a negative and significant impact on poverty in Bengkalis Regency. Bengkalis Regency. This means that when per capita expenditure has increased it will encourage a reduction in poverty. Education has a negative and significant impact on poverty in Bengkalis Regency. This means that when education has increased, it will encourage poverty reduction